From Hospitality to Grace A Julian Pitt-Rivers Omnibus - Pitt-Rivers, Julian (HAU Books, 2017)
The Pitt-Rivers Omnibus brings together the definitive essays and lectures of the influential social anthropologist Julian A. Pitt-Rivers, a corpus of work that has, until now, remained scattered, untranslated, and unedited. Illuminating the themes and topics that he engaged throughout his life-including hospitality, grace, the symbolic economy of reciprocity, kinship, the paradoxes of friendship, ritual logics, the anthropology of dress, and more-this omnibus brings his reflections to new life. Holding Pitt-Rivers's diversity of subjects and ethnographic foci in the same gaze, this book reveals a theoretical unity that ran through his work and highlights his iconic wit and brilliance. Striking at the heart of anthropological theory, the pieces here explore the relationship between the mental and the material, between what is thought and what is done.